Multi-robot coordination strategy for humanoid robot soccer - robocup standard platform league - Hanafi Shafie (2014)
Multi-robot coordination strategy has been a large topic of research within the Robocup teams. Attempts to build a robust team strategy has been met with varying levels of success. Many different kind of strategies have been developed by the Robocup teams over the years. Currently, the NTU Robocup team, Team Nanyang, has no form of multi-robot coordination strategy implemented for its NAO Robots. This project will give an analysis over the different strategies adopted by the Robocup teams, the suggested team strategy for TeamNanyang and the behaviour code to be used.